THE EFFECTS OF a-CHLOROHYDRIN ON THE GESTATION OF THE WISTAR RAT (Rattus norvegicus) - RAHMANIAH RAHMANIAH (BIOTROPIA, 1999)
The investigation of the effects of a-chlorohydrin on the gestation of the wistar rat has been carried out to determine whether a-chlorohydrin could interfere with the gestation of the rat and gestation period for optimal sensitivity. Alpha-chlorohydrin was administered by gavage to three different groups of pregnant rats, namely on the first (pre-implantation period), sixth (early post-implantation period) or fourteenth (late post-implantation period) gestation day, at a single dose of 62.5; 75 and 90 mg/kg body weight. Rats were sacrificed onÂ  the IS* gestation day. Number of implantations, gestation loss and post-implantation mortality were recorded. The results revealed that 75 and 90 mg/kg body weight of a-chlorohydrin significantly interfered with all the gestation periods used. For the pre-implantation group, a-chlorohydrin decreased significantly the implantation number, but increased the gestation loss as well as the post-implantation mortality compared to the control groups. For the early post-implantation and late post-implantation groups, a-chlorohydrin caused a significant increase in post-implantation mortality compared to the control groups. From these results it is concluded that a-chlorohydrin at 75 and 90 mg/kg body weight influences the gestation of the wistar rat administered during the pre-implantation period as the most sensitive gestation period. Key wordsÂ  : a-chlorohydrin//tattu? norvegi'ctu/rat/pre-implantation/early post-implantation/late post-implantation/implantation/gestation loss/post-implantation mortality.